Investigation on product innovation performance in small medium enterprise in Malaysia - Abu Bakar, Lily Julienti; Ahmad, Hartini (2013)
In view of the fact that there has been a dramatic increase in Malaysia SMES development, this research reviews the tangible and intangible resources and its contribution to innovation development. In the context of Malaysia manufacturing companies, both resources have been found given the highest impact on the product innovation performance.Intangible resources is perceived to be important from a strategic point of view.since it bring together more frequently the requirements necessary for producing sustainable advantage: that are valuable, rare and inimitable and non substitutable.Survey was distributed randomly to the business owners and managers who work in various sizes of manufacturing firms.